TPST2-mediated receptor tyrosine sulfation enhances leukocidin cytotoxicity and S. aureus infection - He, Jie; Yang, Xianggui; Yang, Kai; Xu, Honglin; Chen, Cheng; Wang, Junxiong; Zeng, Jun (Frontiers in Immunology, 2023)
Background: An essential fact underlying the severity of S. aureus infection is the bicomponent leukocidins that the pathogen releases to target and lyse host phagocytes through specifically binding cell membrane receptors. However, little is known about the impact of post-transcriptional modification of receptors on the leukocidins binding.In this study, we used siRNA library (horizon/Dharmacon) to screen potential genes that affect leukocidins binding on receptors. The cell permeability was investigated through flow cytometry measureing internalization of DAPI. Expression of C5aR1, sulfated C5aR1 in, and binding of 6x-His-tagged HlgC and LukS-PV to THP-1 cell lines was detected and analyzed via flow cytometry. Bacterial burden and Survival analysis and experiment was conducted in WT and myeloid TPST-cko C57BL/6N mice.Results: After shRNA knowdown of TPST2 gene in THP-1, HL-60 and RAW264.7, the cytotoxicity of HlgAB, HlgCB and PVL on THP-1 or HL-60 cells was decreased significantly, and the cytotoxicity of HlgAB on RAW264.7 cells was also decreased significantly. Knockdown of TPST2 did not affect the C5aR1 expression, but downregulated cell surface C5aR1 tyrosine sulfation on THP-1. And we found that the binding of HlgC and LukS-PV on cells surface receptor C5aR1 was